“Iron triangle” of regulating the uterine microecology: Endometrial microbiota, immunity and endometrium - Zhu, Na; Yang, Xuyan; Liu, Qiao; Chen, Yahui; Wang, Xiaolan; Li, Huanhuan; Gao, Hong (Frontiers in Immunology, 2022)
The uterus is the core place for breeding new life. The balance and imbalance of uterine microecology can directly affect or even dominate the female reproductive health. Emerging data demonstrate that endometrial microbiota, endometrium and immunity play an irreplaceable role in regulating uterine microecology, forming a dynamic iron triangle relationship. Up to nowadays, it remains unclear how the three factors affect and interact each other, which is also a frontier topic in the emerging field of reproductive tract microecology. From this new perspective, we aims to clarify the relationship and mechanism of the interaction of these three factors through the description of six aspects, including effect of endometrium on immunity, effect of immunity on endometrium, effect of immunity on endometrial microbiota, effect of endometrial microbiota on immunity, effect of endometrium on endometrial microbiota and effect of endometrial microbiota on endometrium. Finally, the limitations and future prespectives of the current studies are summarized. These findings can provide new insights and measures for the regulation of uterine microecology, the prevention and treatment of endometrial diseases, and the further multi-disciplinary integration between microbiology, immunology and reproductive medicine.